Feasibility of slotted end connections improved with thicker sections in tension: Experimental and numerical investigation. (September 2021) - Liu, Z.Q.; Lin, Y.; Luo, B.; Wang, Q.; Zhang, W.T.
Abstract: Gusset plate slotted end connections are effective and convenient techniques for connecting tubular members in building structures. A net section crack is the dominant failure mode found in conventional slotted end connections unless strengthening measures are adopted. The improved connection involves a thick-walled circular hollow section (CHS) set at both ends of the member to increase the area of the net section. A series of laboratory tests and associated numerical models were conducted to investigate the mechanical performance of the improved slotted end connection under axial tensile loading. The load-displacement relationship, stress distribution characteristics, and typical failure modes are all incorporated and discussed. Different from tear-out failure or net section crack failure in a conventional connection, the improved connection shows gross section cracks after experiencing extensive gross section yielding. The improved connection enables the length of the fillet weld (LW ) to be greatly reduced without causing a reduction in the load-bearing capacity. With the gradual increase in the length of the fillet weld (LW = 60, 90, and 120 mm), the axial load-bearing capacity of the improved connection is approximately 34.6%, 15.8%, and 4.9% higher than that of the conventional connection, respectively. From the validated FE analysis, the local stress concentration near the slot end can be reduced by approximately 50%, and the shear lag has little effect on the strength of the net section. The load-bearing capacity, ductility, and failure modes of the improved connection show better performance than those of the conventional connection. Graphical abstract: Unlabelled Image Highlights: The failure modes of conventional slotted end connection are closely related to the insertion length of the gusset plate (LW ). When LW ranges from 0.9D to 1.5D, the conventional connection occur tear-out failure along the fillet weld or the net section fracture failure. For the improved slotted end connection mainly occurs full section fracture failure modes of the thinner steel tube (LW ≥ 0.9D) and showing better ductility characteristic. For the improved slotted end connections, the stress concentration near the slot is almost 50% lower than that of the conventional one. And the improved connection area keep elastic when the maximum load reached. The crack failure of the improved specimen occurred in the mid-length of the specimen, which can effectively guarantee the design concept of strong joints and weak members. Increasing the extension length (Le) of the thick-walled steel tube can reduce the influence of shear lag on the distribution of tensile stress, and effectively improve the uniformity of the tensile stress distribution from the strengthened gusset plate joint to the thinner steel tube. And when Le ≥ 0.6*(Ds -tg ), the tensile stress distribution of thinner steel pipe showing uniformly. Increasing the thickness of the thick-walled steel tube (t0 ) can effectively increase the strength of the joint region and suppress the local fracture caused by shear lag. It is suggested that the wall thickness of the strengthening section t0 = 1.5ts, to ensure the strength of the slotted end connection to be effectively guaranteed.